2018
DOI: 10.1186/s12872-018-0913-2
|View full text |Cite
|
Sign up to set email alerts
|

The safety of catheter ablation for premature ventricular contractions in patients without structural heart disease

Abstract: BackgroundPatients with frequent premature ventricular contractions (PVCs) are often symptomatic. Catheter ablation was usually indicated to eliminate symptoms in patients with PVCs-induced cardiomyopathy. Currently, PVCs-ablation is also applied for patients with PVCs and no structural heart diseases (SHD); however, the safety and efficacy of ablation in these patients remains unclear.MethodsIn this retrospective study, data from patients who underwent ablation for PVCs from January 2010 to December 2016 at o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 16 publications
2
17
0
1
Order By: Relevance
“…Regarding catheter ablation of VOT-PVCs, the acute success rate in published series ranged from 77% to 97%, while the long-term success rate ranged from 77% to 83%. [13][14][15] The results of the current study were similar to the overall success of ablation for PVCs reported in the literature. [13][14][15] In the group with acute procedural success, 16 patients still had sporadic PVCs within the first 24-h post-ablation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Regarding catheter ablation of VOT-PVCs, the acute success rate in published series ranged from 77% to 97%, while the long-term success rate ranged from 77% to 83%. [13][14][15] The results of the current study were similar to the overall success of ablation for PVCs reported in the literature. [13][14][15] In the group with acute procedural success, 16 patients still had sporadic PVCs within the first 24-h post-ablation.…”
Section: Discussionsupporting
confidence: 87%
“…[13][14][15] The results of the current study were similar to the overall success of ablation for PVCs reported in the literature. [13][14][15] In the group with acute procedural success, 16 patients still had sporadic PVCs within the first 24-h post-ablation. These patients might have deeper PVC origins than patients that achieved total elimination of PVCs, resulting in a hindered radiofrequency energy delivery to the PVC origin during catheter ablation.…”
Section: Discussionsupporting
confidence: 87%
“…Published success rates of RF ablation for VPBs from the RVOT have been excellent and range from 93% to 97.1% [5][6][7] ; however, very few pediatric patients were included in these studies. Further, complication rates published from these investigations focused on acute complications like acute cardiac events or those related to vascular access.…”
Section: Discussionmentioning
confidence: 99%
“…RFCA allowed a significant decrease in PVCs in the LV. 24 Atrioventricular conduction block occurred in 2 patients. In patients with arrhythmias originating from high risk regions conservative treatment may be the option of choice.…”
Section: Left Ventricular Function Improvementmentioning
confidence: 99%